Macadamia Biodiesel as a Sustainable and Alternative Transport Fuel in Australia. (March 2017) - Azad, Abul Kalam; Rasul, Mohammad; Khan, M. Masud; Sharma, Subhash
Abstract: The study investigated the prospect of Macadamia biodiesel as a sustainable and alternative fuel for diesel engine in the transport sector in Australia. The crude vegetable oil is converted to biodiesel by the transesterification reaction with potassium methoxide as a catalyst at 60 °C for one hour. The fatty acid composition and fuel properties of the converted biodiesel are tested under the ASTM and EN standards and compared those with the properties of Ultra-low Sulphur diesel (ULSD). A 4 cylinder, four strokes, DI diesel engine performance and emission characteristics were studied using B5 (5% biodiesel + 95% ULSD by vol.) and B20 (20% biodiesel + 80% ULSD by vol.) blends. The experiment was conducted at full load condition by varying engine speed from 1200 rpm to 2400 rpm. The study examined the brake specific fuel consumption (BSFC) and brake thermal efficiency (BTE) as engine performance parameters and CO, CO2, HC, PM, NOx, and EGT as emission parameters and compared these with results of ULSD. The study found minimum BSFC and maximum BTE at 1600 rpm engine speed. The result reveals that Macadamia biodiesel has higher BSFC, about 5% (B5) to 10% (B20) and lower BTE, about 4.5% (B5) to 6.8% (B20) throughout the range of engine speed. Significant reduction in CO, HC, and PM emissions were found. More specifically, an average reduction of 26% (B5) to 40% (B20) in CO; about 9% (B5) to 31% (B20) in HC; 15% (B5) to 33% (B20) in PM emission were found compared to ULSD. However, the higher EGT of the biodiesel blends increases NOx emission, about 21% to 27% compared to ULSD. Further study on tribological characteristics of Macadamia biodiesel is recommended before any commercial application can be made.